(untitled) (Research, Society and Development, 2021)
Objective: To analyze the process of brain death diagnosis, besides characterizing the profile of organ and tissue donors. Methods: Analysis of medical records of 203 patients with suspected brain death monitored by the Central de notificação, captação e distribuição de órgãos do norte de Minas Gerais, between 2013 and 2016. Results: Male individuals were the most prevalent (62%), with a mean age of 40.4 years (16.6), the main cause of brain death being traumatic brain injury (44.5%), followed by stroke (43.6%). As for complementary exams, transcranial Doppler and cerebral arteriography were used to confirm brain death in 82.3% and 16.2% of cases, respectively. The percentage of effective donors in the population studied was 41% and the average effective donor rate per million population between 2013 and 2016 in northern Minas Gerais was 12.5. Conclusion: The transcranial Doppler showed execution time and resolution similar to the gold standard. The rate of effective donations in northern Minas Gerais was higher than the state and national average, while the estimated rate of identification of potential organ donors was below the national average and most developed countries.